Gender, Space, and Religious Privacy in Amsterdam - Da Silva Perez, Natália; Kristensen, Peter Thule (TSEG - The Low Countries Journal of Social and Economic History, 2021)
Silva Perez and Kristensen examine the intersection of gender and religious traditions for the use of space for two distinct religious groups: the Amsterdam beguines, a Catholic community, and the Portuguese Nation, a Jewish community. In the religiously diverse environment of seventeenth century Amsterdam, only the Dutch Reformed Church was officially authorized to have visible places of worship. Unsanctioned religious groups such as the beguines and the Portuguese Nation had to make arrangements to regulate visibility and access to their spaces of worship. Using privacy as an analytical lens, the authors discuss how strategies employed by the two groups changed over the course of the century.